HUBUNGAN KARAKTERISTIK IBU NIFAS DENGAN PENGETAHUAN ASI EKSLUSIF DI KABUPATEN BREBES - Rosmalia Kamil; Silpi (Lembaga Penelitian & Pengabdian Masyarakat Sekolah Tinggi Ilmu KesehatanBrebes, 2023)
Background: Breast milk is the main and first food for newborns and the best and natural, containing all nutrients as needed for optimal growth and development of babies. The problem of exclusive breastfeeding is that there is still a low understanding of postpartum mothers, families and communities about exclusive breastfeeding. The habit of giving food or drink early from some people also triggers the lack of success in exclusive breastfeeding. Exclusive breastfeeding is the provision of breast milk (ASI) without food and drink (including lemon juice, honey, sugar water), which starts from newborn (BBL) until the age of 6 months. The purpose of this study is, To determine the relationship between the characteristics of postpartum mothers with Exclusive Breastfeeding Knowledge in PMB Mrs. S Kluwut Village in 2022. Methods: This research is an analytical descriptive research. The population in this study is postpartum mothers totaling 48 people in PMB Mrs. S Kluwut Village, Brebes Regency. Total sampling data collection technique, the total sample used in this study was 48 people. Univariate and bivariate data analysis was then analyzed with Chi square statistical tests. Results: The results showed a relationship between maternal education and maternal knowledge about exclusive breastfeeding (p 0.023 < 0.05), there was a relationship between work and maternal knowledge about exclusive breastfeeding (p 0.000 < 0.05), there was a relationship between parity with maternal knowledge about exclusive breastfeeding (p 0.036 < 0.05). Conclusion: The results showed that there was a relationship between education, work, and maternal parity with maternal knowledge about exclusive breastfeeding with a p value of < 0.05. The need to provide counseling about exclusive breastfeeding not only to postpartum mothers, but also to women of childbearing age so that knowledge about exclusive breastfeeding becomes better.